Assessing the Preparedness of English as a Foreign Language (EFL) Teachers in Implementing the 2022 National Curriculum at Senior High Schools - Kurnia Saputri; Urip Sulistiyo; Mukhlash Abrar (STAI Hubbulwathan Duri, 2024)
This research aimed to assess the preparedness of EFL teachers for implementing the IKM at senior high schools in Palembang City. The research used mixed methods. Both of the data were collected concurrently. When self-developed and validated questionnaires were distributed and filled in, to know the general overview of the EFL teachers in implementing the IKM. For data triangulation, the interview data was supported by a teaching document in the form of a lesson plan (RPP). The overall result of quantitative data analysis showed that the EFL teachers of SHSs were highly ready in terms of competencies, assessment methods, mindset/attitude, commitment, and teaching resources to implement the IKM. Meanwhile, the analysis of qualitative data indicated that EFL teachers had not yet demonstrated their readiness to implement IKM according to the process standards of IKM teaching. This less-readiness was caused by the provided training, and the workshop was only able to enhance their cognitive aspects, not the practical knowledge required to implement the IKM properly. The findings of this research shed light on policymakers and leaders about the EFL teachers' readiness toward the IKM implementation in Palembang City.